Nonlinear analysis of right atrial electrograms predicts termination of persistent atrial fibrillation within the left atrium by catheter ablation. (10th February 2016) - Luca, Adrian; Buttu, Andrea; Pruvot, Etienne; Pascale, Patrizio; Bisch, Laurence; Vesin, Jean-Marc
Abstract: The termination of long-standing persistent atrial fibrillation (LS-pAF) can be achieved by stepwise catheter ablation (step-CA) within the left atrium (LA). Our study aims to applying complexity measures derived from nonlinear time series analysis in order to characterize LS-pAF in terms of organization and to identify patients in whom AF can be terminated from those in whom AF cannot be terminated by step-CA within the LA. A total of 33 consecutive patients (age 61  ±  7 years, sustained AF duration 19  ±  11 months) with LS-pAF underwent step-CA. The organization of right bipolar electrograms before and during the ablation procedure was assessed using the coarse-grained correlation dimension. LS-pAF was terminated into sinus rhythm or atrial tachycardia in 22 patients during step-CA within the LA (left terminated patients—LT). In 11 patients the ablation procedure failed to terminate AF within LA (not left terminated patients—NLT). The statistical analysis of the estimated coarse-grained correlation dimension revealed that a higher right atrial (RA) organization before step-CA was associated to AF termination within the LA. During the ablation procedure, the level of RA organization displayed distinctive evolution between LT and NLT patients with a significant organization increase before AF termination for the LT patients.